PEMANFAATAN MEDIA DIGITAL BERBASIS VIDEO ANIMASI CANVA DALAM PEMBELAJARAN DAERAHKU YANG BERSEJARAH MATERI WARISAN BUDAYA KEKAYAAN DAERAH NUSANTARA KELAS V SD - Wulan Mahmuda Alfani; Siti Mayang Sari; T.M Haekal (STKIP Subang, 2026)
This study aims to describe the utilization of digital media based on animated videos using the Canva application in the learning of “My Historical Region” on the topic of cultural heritage of the Indonesian archipelago in Grade V of elementary school. This study is motivated by the lack of varied, engaging, and contextual learning media, which impacts students’ low understanding and participation in the learning process. The method used is a qualitative approach with a descriptive research design. The research subjects consist of teachers and fifth-grade students. Data collection techniques include observation, interviews, and documentation. Data analysis is carried out through the stages of data reduction, data display, and conclusion drawing. The results show that the use of Canva-based animated video media is able to create a more engaging, interactive, and enjoyable learning atmosphere. Students appear more active in participating in the learning process and find it easier to understand the material on local cultural heritage. In addition, this media helps teachers deliver the material more clearly and systematically. However, several challenges are identified, such as limited technological facilities and teachers’ skills in operating digital media. Thus, it can be concluded that Canva-based animated video media plays an important role in supporting effective and meaningful learning processes, especially in materials related to cultural and historical contexts.